Orwell's roses - Solnit, Rebecca 1961- (Viking, 2021)
"A fresh take on George Orwell as a far more nature-loving figure than is often portrayed, and a dazzlingly rich meditation on roses, gardens, and the value and use of beauty and pleasure in the face of brutality and horror. "In the spring of 1936 a man planted roses." That man was George Orwell, shortly before he went off to fight against fascism in Spain. Today, those rosebushes are still thriving. This is the starting point for Rebecca Solnit's new book, which presents another side of Orwell, a neglected arcadian Orwell who took enormous pleasure in the natural world and found great meaning and value in it. Orwell's planting of the roses is an axle from which Solnit's chapters radiate out like spokes as she brilliantly explores its various contexts, perspectives, and meanings, following the contours of Orwell's life and tracking how deeply enmeshed the love of nature is in all his writing.
Contents: I The Prophet and the Hedgehog: One Day of the Dead 3- Two Flower Power 15- Three Lilacs and Nazis 21- - II Going Underground: One Smoke, Shale, Ice, Mud, Ashes 51- Two Carboniferous 57- Three In Darkness 63- - III Bread and Roses: One Roses and revolution 77- Two We Fight for Roses Too 85- Three In Prais Of 91- Four Buttered Toast 101- Five The Las Rose of Yesterday 109- - IV Stalin's Lemons: One The Flint Path 121- Two Empire of Lies 131- Three Forcing Lemons 143- - V Retreats and Attack: One Enclosures 149- Two gentility 157- Three Sugar, Poppies, Teak 165- Four Old Blush 171- Five Flowers of Evil 179- - VI The Price of Roses: One Beauty Problems 187- Two In the Rose Factory 195- Three The Crystal Spirit 205- Four The Ugliness of Roses 213- Five snow and Ink 221- - VII The River Orwell: One An Inventory of Pleasures 235- Two "As the Rose-Hip to the Rose" 251- Three The River Orwell 265- - Gratitude 269- Notes 273- Image Credits 295- Index 297-
Keywords: Orwell, George -- 1903-1950; Gartenarbeit; Orwell, George / 1903-1950; Authors, English / 20th century / Biography; Orwell, George / 1903-1950 / Homes and haunts; Orwell, George / 1903-1950 / Knowledge and learning; Roses; Gardening; Nature; BIOGRAPHY & AUTOBIOGRAPHY / Literary Figures; NATURE / General; LITERARY CRITICISM / Subjects & Themes / Nature; Authors, English; Homes; 1900-1999; Biography; Biographies